A Multi-Interface Platform System for Assistance and Evaluation of Disabled People - Chadi Fouad Riman; Hector Peralta; Eric Monacelli; Yasser Alayli; Ali El Hajj; Imad Mougharbel (Applied Bionics and Biomechanics)
In this work, an evaluation and assistance platform for people with disabilities is presented. This platform allows the control of different systems (PC games, robot, electric wheelchair) using different interfaces (mouse, joystick, etc.). The software facilitates the saving of experimental data for analysis, it can be automatically reconfigured to match user’s ability, and it is operated locally or remotely through the internet. Quantitative indicators are defined for evaluation purposes and to determine the needed assistance and adaptation. The system is tested and results are presented and discussed.